Encyclopedia of Native American music of North America - Keillor, Elaine, 1939-; Archambault, Tim; Kelly, John M. H. (Greenwood, an imprint of ABC-CLIO, LLC, 2013)
"Encyclopedia of Native American Music of North America documents the surprisingly varied musical practices among North America's First Peoples, both historically and in the modern context. It supplies a detailed yet accessible and approachable overview of the substantial contributions and influence of First Peoples that can be appreciated by both native and nonnative audiences, regardless of their familiarity with musical theory. The entries address how ethnomusicologists with Native American heritage are revolutionizing approaches to the discipline, and showcase how musicians with First Peoples' heritage are influencing modern musical forms including native flute, orchestral string playing, gospel, and hip hop. The work represents a much-needed academic study of First Peoples' musical cultures--a subject that is of growing interest to Native Americans as well as nonnative students and readers"--Provided by publisher.